Interfacial Molecule Control Enables Efficient Perovskite Light‐Emitting Diodes - Ye, Yong‐Chun; Shen, Yang; Zhou, Wei; Feng, Shi‐Chi; Wang, Jiang‐Ying; Li, Yan‐Qing; Tang, Jian‐Xin (Advanced functional materials, 2023)
Perovskite light‐emitting diodes (PeLEDs) are emerging as promising candidates for new‐generation high‐definition displays with excellent color purity and low power consumption. Nevertheless, the massive defects at grain boundaries and severe interfacial exciton quenching are critical challenges that hinder the commercialization process of PeLEDs. Herein, a novel and feasible strategy of interfacial molecule control is demonstrated by employing a bifunctional material with abundant phosphine oxide groups to induce strong interaction and exciton management between the perovskite and electron‐transport layers (ETLs). This modification layer is capable of passivating the surface crystal defects and blocking the interfacial exciton transfer simultaneously, contributing to minimized energy loss at the interface. Consequently, the modified PeLEDs with green (at 513 nm), blue (at 488 nm), and red (at 666 nm) emissions achieve maximum external quantum efficiencies of 18.8%, 12.6%, and 12.3%, respectively. This study reveals the importance of interfacial molecule control for reducing the energy loss in PeLEDs. A rational interface engineering is demonstrated by regulating the molecular characteristics between perovskite and electron‐transport layers for suppressing the trap‐mediated nonradiative recombination and undesirable exciton quenching, yielding green, blue, and red light‐emitting diodes with external quantum efficiencies of 18.8%, 12.6%, and 12.3%, respectively.